2000
DOI: 10.1046/j.1365-2036.2000.00758.x
|View full text |Cite
|
Sign up to set email alerts
|

High incidence of reflux oesophagitis after eradication therapy for Helicobacter pylori: impacts of hiatal hernia and corpus gastritis

Abstract: Eradication of H. pylori increased the prevalence of reflux oesophagitis in our patient group. The presence of hiatal hernia and corpus gastritis are closely related to the development of reflux oesophagitis after H. pylori eradication therapy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

13
185
9

Year Published

2006
2006
2022
2022

Publication Types

Select...
3
2
2

Relationship

0
7

Authors

Journals

citations
Cited by 163 publications
(207 citation statements)
references
References 32 publications
13
185
9
Order By: Relevance
“…In one study from Japan, the cumulative prevalence of reflux oesophagitis after H. pylori eradication was 26% in patients with hiatal hernia, 8% in those without hiatal hernia, 33% in those with corpus atrophic gastritis and 13% in those without corpus atrophic gastritis. 5 A second finding in our study was that heartburn and regurgitation improve significantly after eradication therapy in patients with antrum-predominant gastritis. This is likely related to correction of the acid hypersecretion that occurs in these patients.…”
Section: Discussionsupporting
confidence: 55%
See 2 more Smart Citations
“…In one study from Japan, the cumulative prevalence of reflux oesophagitis after H. pylori eradication was 26% in patients with hiatal hernia, 8% in those without hiatal hernia, 33% in those with corpus atrophic gastritis and 13% in those without corpus atrophic gastritis. 5 A second finding in our study was that heartburn and regurgitation improve significantly after eradication therapy in patients with antrum-predominant gastritis. This is likely related to correction of the acid hypersecretion that occurs in these patients.…”
Section: Discussionsupporting
confidence: 55%
“…26 Two randomized controlled trials in 603 individuals reported on the development of oesophagitis. The development of reflux symptoms was uncommon, occurring in 6% of individuals undergoing eradication and 3% taking placebo (relative risk: 2, 95% CI: [1][2][3][4][5]. Differences between these studies are probably related to the small sample sizes, which make it difficult to detect an uncommon event, differences in the pattern of gastritis in the different populations studied and the lack of a randomized control group in others.…”
Section: Discussionmentioning
confidence: 90%
See 1 more Smart Citation
“…A previous reflux disease hidden by peptic ulcer disease (28) , population differences (9) and methodological differences can justify these conflicting results.…”
Section: Discussionmentioning
confidence: 96%
“…The authors reported a higher rate of esophagitis in patients who had their H. pylori eradicated compared to the group in which the infection had continued. Following this first study, other trials were carried out, either confirming LABENZ' work (8,9,14) or reporting contradictory results (1,24,36,38,41,42,44) .…”
Section: Introductionmentioning
confidence: 99%